The complete poems - Constable, Henry 1562-1613 (PIMS, Pontifical Institute of Mediaeval Studies, 2023)
"Elizabethan poet Henry Constable (1562-1613), a Protestant-born Catholic convert, was long dismissed as a minor poet, a Catholic traitor, or both, but his writings reveal unresolved tensions between the public and the private, hope and disillusion, the secular and the religious. This book offers a new comprehensive critical edition of Constable's sonnets. Along with an updated biography and a study of the sonnet collections, the introduction provides an authoritative revision of the canon of Constable's poetry and an overview of its critical reception."
Keywords: Constable, Henry / 1562-1613; Sonnets, English; Quelle